Linking sedimentary sulfur and iron biogeochemistry to growth patterns of a cold‐water coral mound in the Porcupine Basin, S.W. Ireland (IODP Expedition 307). Issue 5 (8th June 2015) - Wehrmann, L. M.; Titschack, J.; Böttcher, M. E.; Ferdelman, T. G.
Abstract Challenger Mound, a 150‐m‐high cold‐water coral mound on the eastern flank of the Porcupine Seabight off SW Ireland, was drilled during Expedition 307 of the Integrated Ocean Drilling Program (IODP). Retrieved cores offer unique insight into an archive of Quaternary paleo‐environmental change, long‐term coral mound development, and the diagenetic alteration of these carbonate fabrics over time. To characterize biogeochemical carbon–iron–sulfur transformations in the mound sediments, the contents of dithionite‐ and HCl‐extractable iron phases, iron monosulfide and pyrite, and acid‐extractable calcium, magnesium, manganese, and strontium were determined. Additionally, the stable isotopic compositions of pore‐water sulfate and solid‐phase reduced sulfur compounds were analyzed. Sulfate penetrated through the mound sequence and into the underlying Miocene sediments, where a sulfate–methane transition zone was identified. Small sulfate concentration decreases (<7 mm) within the top 40 m of the mound suggested slow net rates of present‐day organoclastic sulfate reduction. Increasing δ34S‐sulfate values due to microbial sulfate reduction mirrored the decrease in sulfate concentrations. This process was accompanied by oxygen isotope exchange with water that was indicated by increasing δ18O‐sulfate values, reaching equilibrium with pore‐water at depth. Below 50 mbsf, sediment intervals with strong 34S‐enriched imprints on chromium‐reducible sulfur (pyrite S), high degree‐of‐pyritization values, and semi‐lithified diagenetic carbonate‐rich layers characterized by poor coral preservation, were observed. These layers provided evidence for the occurrence of enhanced microbial sulfate‐reducing activity in the mound in the past during periods of rapid mound aggradation and subsequent intervals of non‐deposition or erosion when geochemical fronts remained stationary. During these periods, especially during the Early Pleistocene, elevated sulfate reduction rates facilitated the consumption of reducible iron oxide phases, coral dissolution, and the subsequent formation of carbonate cements.